Moving beyond depression screening: integrating perinatal depression treatment into OB/GYN practices. (2019) - Terrazas, Christina; Segre, Lisa S.; Wolfe, Cheryl
Abstract : In 2015, the American College of Obstetricians and Gynecologists issued a recommendation to screen women for depression and anxiety symptoms at least once during the perinatal period. Nevertheless, many identified women will not receive care from a behavioral health specialist. Listening Visits (LV), developed for delivery by nurses and validated in the United Kingdom, have recently been evaluated in a US-based randomized controlled trial (RCT) which recruited research participants from three home-visiting programs and an urban OB/GYN practice. RCT results indicated clinically and significant improvement in depression symptoms. To bridge the gap between evidence and practice, and based on experiences garnered at the OB/GYN site during the RCT, this development paper proposes a strategy for implementing depression screening and LV into routine clinical care in this practice setting.